Towards a Model of Convention Bureau Competitiveness (Global Journal of Management and Business Research, 2021)
Convention bureaus play a pivotal role in bidding for destination events such as international congresses and conventions. Although competition to host business events is increasing from a growing number of rival destinations, there has been very limited research to date exploring the determinants that contribute to the efficacy of a convention bureau. This investigation adopts a qualitative exploration of the elements of convention bureau effectiveness. Interviews with twenty-five meeting planners and senior convention bureau staff has revealed that having core resources but also additional support with visa applications can give convention bureaus a competitive advantage. Additionally, bureaus that have access to a range of destination stakeholders to include business leaders, and can demonstrate that they are experienced and trustworthy are considered to be more competitive. The results of this investigation are presented in the first model of convention bureau competitiveness which is a tool that can be used to underpin business tourism policy and strategy in the management of destinations.
Keywords: convention bureau; destination management; convention bureau competitiveness; policy; business tourism